Estudo descritivo sobre os pacientes atendidos no ambulatório de geriatria do HUJBB, no período de março de 2003 a agosto de 2006 - PINHEIRO, Gracivaldo Castro (2022)
Population aging is a worldwide phenomenon and one of the biggest challenges to contemporary public health systems. According to statistical forecasts from the World Health Organization, the epidemiological scenario in Brazil (in relation to mortality caused by diseases) indicates a shift from the currently prevailing contagious diseases of younger people towards typical noninfectious chronic diseases of the elderly ones. Thus, dementia like illnesses such as Alzheimer‟s disease will get epidemic proportions in consequence of population aging. The aim of this research is to describe the clinical and epidemiological profile of the elderly population treated at the geriatric clinic of Hospital Universitario Joao de Barros Barreto (HUJBB, a hospital affiliated to the School of Medicine of the Federal University of the State of Para, Brazil), emphasizing functional cognitive findings. HUJBB is a well-known hospital in northern Brazil for its psychiatric department, especially concerning Alzheimer‟s disease. A descriptive survey was carried out through data collection from patients‟ medical records in association with the use of research protocol of patients registered from March/2003 to August/2006. The hospital‟s Ethics Committee approved the research project. Most patients were women (67%), between 71 and 80 years old (44.3%), with secondary education (28.9%). Regarding image examination (neuroimaging), 58.8% underwent brain scan through computed tomography (CT) and 6.2% through functional magnetic resonance imaging (fMRI). As for the diagnosis, 60.8% were diagnosed with dementia, 16.5% as having light cognition disorder and 30.9% with depression associated or not with symptoms of cognition disorder. The probable cause (etiology) for 59.3% of the patients diagnosed with dementia was Alzheimer‟s disease in a moderate stage. Therefore, although the concept of dementia as unavoidable consequence of aging is rather outdated, difficulties concerning its diagnosis (etiology) continue to exist, especially in its early stages when, commonly, the patient is not aware of his cognition problems or tries to minimize or disguise them. Even so, routine evaluation of cognitive functions continues to be notoriously neglected as a compulsory examination in medical consultations.